Opportunities, challenges, and contextual supports to promote enacting maturing during adolescence - Ballard, Parissa J.; Hoyt, Lindsay Till; Johnson, Jasmine (Frontiers in Psychology, 2022)
Conceptions of adolescent “storm and stress” may be tied to a developmental mismatch that exists between young people’s need for meaningful roles and autonomy - which we refer to as a need for enacting maturity - and the lack of such opportunities in most adolescents’ contexts. First, we summarize our previous work on enacting maturity, including a review of the key components, links to well-being, and the nuances and limitations of this construct. Next, we extend this work by considering how the ecological contexts (e.g., family, school, community) young people are embedded in and their various intersecting social positions and identities (e.g., race/ethnicity, gender, immigrant origin) influence their experiences with enacting maturity. In this section, we pose several key questions for developmental scientists around: (a) identifying a young person’s desire for, and phenomenological processing of, their adult-like roles, (b) understanding how complex and unequal responses to physical maturation shape opportunities for enacting maturity, and (c) attending to disparities in curricular and extracurricular pathways to leadership, responsibility, and autonomy. Finally, we discuss spaces with high potential to support enacting maturity, including both specially-designed programs (e.g., youth participatory action research, leadership programs) as well as routine, everyday opportunities (e.g., interactions with teachers, training for companies that employ youth). We offer two levers for supporting enacting maturity across both types of spaces: adult allies and responsive organizations. Looking to exemplary programs, innovative leaders, social media, and case studies, we re-imagine how adults and organizations can promote young people enacting maturing in ways that are safe, worthwhile, and equitable.